PENINGKATAN KINERJA GURU MELALUI BUDAYA KERJA - Mursito, Hardian; Setiawati, Nur Amega; Djuhartono, Tjipto (Universitas Indraprasta PGRI, 2019)
The purpose of this study was to determine the improvement of teacher performance through work culture. The research method used is a survey method with quantitative approach. In determining popolation and the sample using the entire population as a sample (saturated sample). The results of the study can be concluded that there is a positive and significant influence between work culture on teacher performance. From the calculation results obtained by the number R is equal to 0.121 which means that the influence of work culture on teacher performance is equal to 0.121 which indicates that the influence is low